Prevalence of Salmonella in poultry processing environments in wet markets in Penang and Perlis, Malaysia - Hafiz, Nidaullah; Nadarajan, Abirami; Ahamed Kamal, Shamila Syuhada; Chuah, Li Oon; Huda, Nurul; Tan, Teik Pei; Zainal Abidin, Farah Wahida; Rusul, Gulam (Veterinary World, 2017)
Aim: The aim of this study was to determine the prevalence of various Salmonella serotypes in chickens, carcass contact surfaces as well as environmental samples collected from wet markets and small scale processing plant. Materials and Methods: A total of 182 poultry and environmental samples were collected at random on separate occasions from wet markets and small scale processing plant, during the period of October 2014 to July 2015 in Penang and Perlis, Malaysia. The samples were analyzed for the presence of Salmonella using ISO 6579:2002 conventional culture-based method. Presumptive Salmonella colonies were subjected to various biochemical tests (such as triple sugar iron and lysine iron test), serologically confirmed using polyvalent O and H antisera and further serotyped at Public Health Laboratory, Ministry of Health, Perak, Malaysia. Results: Salmonella serotypes were isolated from 161 out of 182 samples (88.46%) with 100% prevalence in the whole chicken carcass and chicken cuts - as well as transport crate, cage, drum, knife, chopping board, display table, floor, bench wash water, wash water, and drain water. Salmonella was isolated from 91.67%, 83.33%, and 66.67% of defeathering machines, drain swabs, and apron, respectively. 17 serotypes were isolated in this study with Salmonella Albany (57/161), Salmonella Corvallis (42/161), and Salmonella Brancaster (37/161) being the predominant serovars. Conclusion: The most carcass contact and environmental samples collected along the wet market chicken processing line were consistently contaminated with Salmonella. This indicates that Salmonella has established itself in poultry processing environments by colonizing the surfaces of the equipment and survives in these environments by establishing biofilms. Our results highlight the need of implementing strict hygiene and sanitation standards to reduce the incidence of Salmonella. The prevalence of Salmonella in poultry can be reduced effectively by identifying and eliminating the sources and contamination sites during slaughter and processing of poultry.